2019
DOI: 10.3389/fpls.2019.01313
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinformatics Guide to Plant Microbiome Analysis

Abstract: Recent evidence for intimate relationship of plants with their microbiota shows that plants host individual and diverse microbial communities that are essential for their survival. Understanding their relatedness using genome-based and high-throughput techniques remains a hot topic in microbiome research. Molecular analysis of the plant holobiont necessitates the application of specific sampling and preparatory steps that also consider sources of unwanted information, such as soil, co-amplified plant organelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 231 publications
(259 reference statements)
0
35
0
Order By: Relevance
“…Strategies to study the plant microbiome compositions rely on the isolation and identification of cultivable microorganisms (cultivation-dependent), or massive sequencing (cultivation-independent) [ 22 , 23 , 24 ]. The majority of the currently available studies rely on the analysis of next generation sequencing (NGS) datasets from 16S ribosomal RNA gene (16S rRNA) sequences from bacteria or fungi (internal transcribed spacer, ITS) [ 25 ]. However, information on the whole microbiome can be also obtained through whole metagenome shotgun sequencing (WMSS) [ 26 , 27 ], a strategy that allows gathering microbial data at very high depth.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to study the plant microbiome compositions rely on the isolation and identification of cultivable microorganisms (cultivation-dependent), or massive sequencing (cultivation-independent) [ 22 , 23 , 24 ]. The majority of the currently available studies rely on the analysis of next generation sequencing (NGS) datasets from 16S ribosomal RNA gene (16S rRNA) sequences from bacteria or fungi (internal transcribed spacer, ITS) [ 25 ]. However, information on the whole microbiome can be also obtained through whole metagenome shotgun sequencing (WMSS) [ 26 , 27 ], a strategy that allows gathering microbial data at very high depth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, plant microbiome deciphering needs large scale sequencing coverage along with a replication of experiments for robust analysis, and substantial computational and financial support [ 92 , 93 ]. Moreover, the interpretation of data on RNA, microbial DNA, and protein sequence gets hampered due to reduced rates in the high-confidence annotation.…”
Section: Molecular Techniques For Decoding Plant-microbiome Interactimentioning
confidence: 99%
“…Considering some previous studies have suggested that read abundance cannot reliably be used as a proxy for the relative natural abundance of plants in a sample (e.g., [25][26][27][28][29][30]), we compared the taxonomic composition observed when total read counts and total sequence counts were used to generate TAC. In this study, the most appropriate sample for this comparison would be the pooled positive control, given angiosperm, fern, gymnosperm and moss DNA were pooled for sequencing in equal amounts.…”
Section: Differing Approaches To Taxonomic Abundance Chart Generationmentioning
confidence: 99%